2020
DOI: 10.3390/genes11020134
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cytonuclear Coordination of Transcription in Nascent Arabidopsis thaliana Autopolyploids

Abstract: Polyploidy is hypothesized to cause dosage imbalances between the nucleus and the other genome-containing organelles (mitochondria and plastids), but the evidence for this is limited. We performed RNA-seq on Arabidopsis thaliana diploids and their derived autopolyploids to quantify the degree of inter-genome coordination of transcriptional responses to nuclear whole genome duplication in two different organs (sepals and rosette leaves). We show that nuclear and organellar genomes exhibit highly coordinated res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…The allopolyploid individuals will thus contain biparental nuclear chromosomes and uniparental organellar genome inherited from different species, potentially resulting in CNI [51]. Several mechanisms are hypothesized to maintain coordination between organellar and nuclear genomes (reviewed in [51]): down-regulating the expression of the nuclear genes targeted to organelles (of both nuclear genomes or by the preferential expression of the organellar donor), or up-regulating the expression of organellar genes [52]. The study of allopolyploidization influence on CN interactions has mostly been studied on the Rubisco-encoding genes that revealed that maternal genes were preferentially expressed (reviewed in [51]).…”
Section: Cnis Are the Results Of Disrupted Coadaptation Between Organementioning
confidence: 99%
“…The allopolyploid individuals will thus contain biparental nuclear chromosomes and uniparental organellar genome inherited from different species, potentially resulting in CNI [51]. Several mechanisms are hypothesized to maintain coordination between organellar and nuclear genomes (reviewed in [51]): down-regulating the expression of the nuclear genes targeted to organelles (of both nuclear genomes or by the preferential expression of the organellar donor), or up-regulating the expression of organellar genes [52]. The study of allopolyploidization influence on CN interactions has mostly been studied on the Rubisco-encoding genes that revealed that maternal genes were preferentially expressed (reviewed in [51]).…”
Section: Cnis Are the Results Of Disrupted Coadaptation Between Organementioning
confidence: 99%
“…The discrepancies between the former two studies (performed in diploids) and the latter two (performed in polyploids) indicates that cytonuclear stoichiometry may be highly responsive to nuclear gene content. In support of that hypothesis, diverse polyploids appear to compensate for elevated nuclear ploidy with increased organelle genome copy number [40,214,[217][218][219][220]. Additional work investigating the immediate and evolved consequences of cytonuclear stoichiometry at the genomic, transcriptomic, proteomic, and organellar levels, especially by homoeologous pair analysis, will provide valuable insights into the unresolved question of how genome doubling can affect cellular energy production and homeostasis.…”
Section: Cytonuclear Gene Content Evolution In Allopolyploidsmentioning
confidence: 90%
“…1A). There is often a global reduction in expression on a per‐genome basis, combined with differential effects on the regulation of particular classes of genes, notably those that are dosage sensitive (Hou et al, 2018; Coate et al, 2020; Song et al, 2020). Neither overall patterns of methylation nor proximity of transposable elements to genes appears to explain these genome‐wide or gene‐class‐specific phenomena, leaving chromatin folding in space and time (the 4D nucleome; Dekker et al, 2017) as a possible mechanism for coordinated responses of numerous unlinked genes.…”
Section: Figurementioning
confidence: 99%